Monte Carlo Simulation of Optical Light Transport in an Absorption-Based Tapered Fiber Sensor - Mustafa F.H.; Suhailin F.H.; Ismail I.; Mahdi M.A.B. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus